Marma: A New Musical Experimental | Marma: Sebuah Karya Baru Musik Eksperimental - I Dewa Gede Bayu Agastya; I Ketut Sudhana (GHURNITA: Jurnal Seni Karawitan, 2022)
The sensitivity of each human being in capturing cosmic vibrations through the subconscious mind of each is different. Some catch it with full awareness and some with half awareness. The combination of the two is what in Balinese is called "Marma". A person's condition while in a marma situation will allow his five senses to pick up vibrations outside of himself in a different state from reality. The creation of a musical composition is often faced with the abstract and can take ideas from the story of life, nature, objects and so on. The creation of this musical composition takes the idea of Balinese social life in carrying out religious obligations. This work is realized on the basis of the creator who has a passion for a challenge that is able to process the mind, and dares to try to make something a little different through unconventional work. This is what then encourages the creator to make it into the form of experimental musical works, by searching and experimenting with various elements that can be arranged so as to form the originality of an aesthetic work. The creation of this work is as a personal expression to express the thoughts of the creator which is realized through the medium of expressing gamelan.